Development and evaluation of high yielding, multiple disease resistant bread wheat variety - Karan Vandana (DBW187) - Khan, Hanif; Chatrath, Ravish; Kumar, Satish; Mishra, Chandra Nath; Gupta, Vikas; H M, Mamrutha; Jasrotia, Poonam; Bhardwaj, Subhash Chander; Kashyap, Prem Lal; Gangwar, Om Prakash; Kumar, Raj; Prakash, Om; et al. (Journal of Cereal Research, 2025)
Wheat cultivation in India has been primarily dominated by the high productive environments of Indo-Gangetic plains. The North Western and North Eastern Plains are two mega environments for wheat production in the country in terms of area and production. For sustaining the high productivity levels in these areas, a constant demand of improved wheat varieties from the wheat breeding programs is desired. A high yielding bread wheat cultivar DBW187 (Karan Vandana) has been developed and released for cultivation in these areas after testing in trials under AICRP on Wheat and Barley. DBW187 is a high input responsive wheat genotype which has shown a significant yield superiority under early sown irrigated conditions of North Western Plains Zone over the checks HD2967 and HD3086 during 2018-19. Average yield of DBW187 during two years of testing was recorded to be 61.28q/ha. Earlier under evaluation in the North Eastern Plains Zone, this variety has shown an average yield of 48.8 q/ha with a potential yield of 64.7q/ha. The variety was released by Central Sub-committee on Crop Standards, Notification and Release of variety, Ministry of Agriculture, Government of India vide notification No. S.O. 1498(E) dated 01.04.2019 for cultivation in the NEPZ of India and subsequently it was extended to NWPZ vide notification S.O. 98(E) dated 06.01.2020. DBW187 is having a high yield potential along with disease resistance and superior grain quality. The ability to adopt across variable growing conditions in two different zones is a huge advantage for this genotype and will also go a long way in sustaining its cultivation in the region.DOI.10.25174/2582-2675/2020/99622